Minangkabau Cultural Imprints in Hamka’s Tafsīr al-Azhar: Contextualizing the Qur’an through Critical Discourse Analysis - Izzan, Ahmad; Haecal, Mohammad Irfan Farraz; Fitri, Nadya (Postgraduate Studies of UIN Sunan Ampel Surabaya, Indonesia, 2025)
his study explores how Minangkabau literary and cultural elements shaped Haji Abdul Malik Karim Amrullah’s Tafsīr al-Azhar, particularly in the interpretation of al-Baqarah. Employing qualitative content analysis combined with Norman Fairclough’s critical discourse framework, the research examines the interplay between text production, reception, and socio-cultural context in Hamka’s exegetical method. The findings reveal that literary device—such as pantun, proverbs, metaphors, and maxims—serve as key interpretive tools, enriching the text’s aesthetic and cultural resonance. Equally significant are the Minangkabau influences, including local language, social traditions, and political references, which root Qur’anic interpretation in lived experience. This synthesis demonstrates Hamka’s capacity to integrate Islamic revelation with the cultural-linguistic heritage of the Malay-Indonesian world. The study argues that Tafsīr al-Azhar transcends local boundaries, positioning itself within the global discourse of modern Qur’anic exegesis. Hamka’s approach bridges classical interpretive traditions and contemporary cultural realities, highlighting the importance of contextual hermeneutics in making the Qur’an accessible across diverse communities. Ultimately, the study offers a model for culturally grounded tafsīr and provides a foundation for comparative analysis with other modern commentators.